Innovative Surgical Treatment of Severe Cherubism. (January 2019) - Son, Ji H.; Marshall, Danielle C.; Valiathan, Manish; Otteson, Todd; Ferretti, Gerald; Grigorian, Paula A.; Rosen, Carol; Becker, Devra; Rowe, David; Soltanian, Hooman; Lakin, Gregory
Background: Cherubism is an autosomal dominant syndrome characterized by excessive bilateral maxillomandibular bony degeneration and fibrous tissue hyperplasia. Conservative management is the preferred treatment as cherubism has a self-limiting course. Functional or emotional disturbances may, however, demand surgical intervention. We report a patient who underwent surgical intervention. Method/Description: He had significant enlargement of lower cheeks and bilateral lower lid scleral show. On computed tomography of the face, the patient had significant fibrous tissue involving bilateral maxilla and mandible. The mandibular tumor was excised. Given normal inferior border, bilateral sagittal split osteotomy was performed to infracture and inset the outer cortex. During the procedure, patient required blood transfusion intraoperatively, so the maxillary portion of the procedure was delayed until 6 months later. For the maxilla, bilateral transconjunctival approach was used to resect parts of the orbital floors that were concave, resulting in 1 × 2 cm defects bilaterally which were reconstructed using resorbable plates. Then the anterior maxillary tumor was excised. Results: The patient and his parents were satisfied with his appearance after surgery. The patient was noted to have improvement in contour and decreased scleral show. He has most recently followed up 15 months after the initial surgery. There were no long-term complications. Conclusions: Severity of cherubism influences the type of surgical intervention. The present case is innovative because this is the first reported case of recontouring orbital floors with resorbable plates and infracturing of the mandible using sagittal split osteotomies for surgical treatment of cherubism.